Protocol for a prospective cohort study on congenital heart disease in neonates across varied altitudes in Sichuan province, China - Xianmin Wang; JiaXin Liu; Wen Su; Beibei Liu; Lixing Li; Duo Yan; Weiyi Wan; Tongyong Luo (PLoS ONE, 2025)
Congenital heart disease (CHD) is the most prevalent congenital disorder, contributing significantly to neonate mortality. Despite advances in diagnosis and treatment, the incidence and risk factors of CHD remain underexplored, particularly in regions with varied altitudes. Sichuan Province, China, with its diverse topography and altitudes, provides a unique opportunity to investigate the epidemiology of CHD across different environmental settings. This study aims to explore the incidence, subtypes, and risk factors of CHD in neonates across high, middle, and low-altitude regions of Sichuan Province. It also seeks to assess the effectiveness of the Sichuan Province Newborn CHD Free Screening Project, the impact of CHD on family economics and child development, and to provide data-driven recommendations for improving CHD prevention and control measures. We will conduct a multicenter, prospective cohort study involving neonates with positive CHD screening results and their families, recruited from three cities representing different altitude levels: Aba Tibetan and Qiang Autonomous Prefecture, Mianyang City, and Guangyuan City. Data collection will include birth characteristics, CHD screening outcomes, parental and gestational histories, and blood samples for genetic analysis. The study will monitor treatment outcomes, economic impact, and the growth and development of the children over time. This study will provide critical insights into the epidemiology of CHD in Sichuan Province, particularly in relation to altitude. The results will help optimize CHD screening and management programs, ultimately improving outcomes for affected children and their families.